Mode-specific quantum dynamics study of OH+H₂S → H₂O+SH reaction - Xiang, Haipan (2022)
The hydrogen abstraction reaction from H2S by OH is of key importance in understanding of the causes of acid rain, air pollution, and climate change. In this work, the reaction OH+H2S → H2O+SH is investigated on a recently developed ab initio-based globally accurate potential energy surface by the time-dependent wave packet approach under a reduced-dimensional model. This reaction behaves like a barrier-less reaction at low collision energies and like an activated reaction with a well-defined barrier at high collision energies. Exciting either the symmetric or antisymmetric stretching mode of the molecule H2S enhances the reactivity more than exciting the bending mode, which is rationalized by the coupling strength of each normal mode with the reaction coordinate. In addition, the modespecific rate constant shows a remarkable non-Arrhenius temperature dependence.